PENGARUH PERSONAL BRANDING TASYA DI INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN PRODUK MOTHER OF PEARL - Tarina, Miftah; Faaroek, Safiani A.; Resman Muharul (Global Komunika : Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
Social media is the result of the development of technological advances. Instagram is one form of social media. Instagram is the right platform to promote a product, one of which is makeup products that are favored by Indonesian women to support their appearance. Local products innovate and promote to introduce their products to the public and compete with global-scale beauty products to take advantage of beauty influencers on Instagram social media so that the promotional reach can be right on target. One of the most influential beauty influencers for consumers is Tasya Farasya. Tasya Farasya is a beauty influencer who is quite well known on Instagram with strong and attractive personal branding, which can be seen from her always glamorous appearance and honesty in conducting product reviews. Tasya Farasya officially launched her beauty brand "Mother of Pearl" with her first three products. The purpose of this study was to determine the effect of Tasya Farasya's personal branding on Instagram on purchasing decisions for Mother of Pearl products. This study uses the grand theory of S-O-R (Stimulus, Organism, Response). The research method uses a descriptive correlational quantitative approach with a survey method. The population used was 100 respondents with the criteria of Instagram followers Tasya Farasya, women aged 18-34 years, and interested in Mother of Pearl products. The data collection technique used a questionnaire with correlation coefficient and regression analysis techniques. The results of the t-count 3.854 > 1.984, indicate that H0 is rejected and H1 is accepted, meaning that there is an influence of Tasya Farasya's personal branding on Instagram on the purchase decision of Mother of Pearl products.